Acceptance of Kencur Rice Mochi Filled with Asam Turmeric Ice Cream - Hesti Rosmayanti; Sudewi Yogha; Ai Mahmudatussadah (Universitas Pendidikan Indonesia (UPI), 2023)
Mochi is a cake that is liked by many people. In Japan, mochi is included in the Wagashi or also known as sweet dishes that have been consumed since ancient times and are made in a traditional way for the traditional Mochitsuki celebration or known as New Year's celebration. Mochi cake can be modified by using other ingredients or substitutions to increase its functional value. The liquid used in making mochi can be replaced with milk, coconut milk, or other liquids. Rice kencur is a traditional drink that is popular among the people. This traditional drink can be used as an ingredient for liquid in making mochi products. This is included in the development of mochi products, namely Kencur Rice Mochi. The general aim of this research is to determine the acceptability of the kencur rice mochi product filled with sour turmeric ice cream. The method that will be used in this research is an experimental method which is included in the quantitative research method. The research that will be carried out by the author is considered a true experiment. The acceptability or level of liking for this kencur rice mochi product filled with sour turmeric ice cream is very favorable in terms of appearance, color, taste, texture and overall impression because it can be seen from the percentage of acceptability produced, which is 85%. Meanwhile, in terms of aroma, the acceptability percentage value is 83%, which means that people like the product. It can be concluded that kencur rice mochi filled with sour turmeric ice cream is accepted among the public as an innovative product.